2008
DOI: 10.1080/08860220802212890
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Conduction Studies and Prediction of Mortality in Hemodialysis Patients

Abstract: Background. The electrophysiological aspects of uremic neuropathy have been studied extensively, but never for prediction of mortality. In order to assess the parameters of nerve conduction study (NCS) as predictors of mortality in hemodialysis patients, a post hoc analysis of a prospective observation study was made. Methods. We examined conventional electrophysiological parameters (motor nerve conduction velocity [MCV], terminal latency [TL], and F wave latency of the peroneal nerve, as well as sensory nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…From those studies, certain polyneuropathies have been suggested to have substantial disease burden from physical impairments 16,17 or even mortality. 18,19 However, mortality and disease burden quantification of polyneuropathies irrespective of etiology through a large population-based study has not been performed.…”
mentioning
confidence: 99%
“…From those studies, certain polyneuropathies have been suggested to have substantial disease burden from physical impairments 16,17 or even mortality. 18,19 However, mortality and disease burden quantification of polyneuropathies irrespective of etiology through a large population-based study has not been performed.…”
mentioning
confidence: 99%
“…5,38,39 Recently, measures of neuropathy have been shown to significantly correlate with impaired quality of life in diabetic dialysis patients, 8 and with mortality in nondiabetic hemodialysis subjects. 40 The findings of this study suggest that PD may provide a beneficial option for neuropathy management in dialysis patients. Critically, larger cohort longitudinal studies would be required to establish whether early initiation of PD leads to a reduction in overall neuropathy-related disability.…”
Section: Discussionmentioning
confidence: 70%
“…Neuropathy directly contributes to patient morbidity by means of neuropathic symptoms of pain, numbness, and impaired mobility due to reduced sensory feedback and distal weakness which may lead to ulceration and amputation, especially when combined with the microvascular disease that occurs in diabetic patients . Recently, measures of neuropathy have been shown to significantly correlate with impaired quality of life in diabetic dialysis patients, and with mortality in nondiabetic hemodialysis subjects . The findings of this study suggest that PD may provide a beneficial option for neuropathy management in dialysis patients.…”
Section: Discussionmentioning
confidence: 71%
“…After nerve transplantation, there is an increase in nerve conduction due to remyelination 8 . Studies have shown that motor nerve conduction (MCV) is a significant predictor of mortality 13 in hemodialysis patients and achieves statistically significant values: (HR= 0.92; CI (0.86-0.99); p < 0.05) 15 . MCV correlates significantly with dialysis dose; however, further investigation is needed in order to confirm this hypothesis 13 .…”
Section: Nerve Conduction and Quantitation Of Sensory Lossmentioning
confidence: 99%